2001
DOI: 10.1182/blood.v97.12.3931
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeting drugs arsenic trioxide and lonidamine bypass the resistance of TPA-differentiated leukemic cells to apoptosis

Abstract: IntroductionChemotherapeutic drugs can kill cultured leukemic cell lines by inducing apoptosis. 1 This mode of cell death may be clinically relevant because apoptotic blast cells have been detected in the peripheral blood of patients with acute leukemia who received chemotherapeutic drugs. 2 Hallmarks of apoptosis in leukemic cells include characteristic morphologic changes such as cell shrinkage, membrane blebbing, and cell fragmentation into apoptotic bodies, internucleosomal DNA fragmentation, and limited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 63 publications
4
55
0
1
Order By: Relevance
“…These different data were validated by those obtained with VP16 (Figs. 2C-2F), which is known to activate numerous caspases, including caspase-2 (38), and which are in agreement with previous investigations (39,40). So, taken together, our data strongly support an activation of caspase-2 under treatment with 7KC.…”
Section: Analysis By Conventional Fluorescence Microscopy and Flow Cysupporting
confidence: 93%
“…These different data were validated by those obtained with VP16 (Figs. 2C-2F), which is known to activate numerous caspases, including caspase-2 (38), and which are in agreement with previous investigations (39,40). So, taken together, our data strongly support an activation of caspase-2 under treatment with 7KC.…”
Section: Analysis By Conventional Fluorescence Microscopy and Flow Cysupporting
confidence: 93%
“…ATO-induced apoptosis is associated with a loss of inner mitochondrial transmembrane potential and release of cytochrome c into the cytosol [7][8][9]. Experiments with purified mitochondria show that administration of ATO promotes opening of the permeability transition pore, releasing intermembrane proteins, which ultimately cause caspase activation [10]. Caspase induction and activation were also observed in APL cells from patients treated with ATO [1].…”
Section: Introductionmentioning
confidence: 76%
“…Overexpression of Bcl-2, that modulates the activity of BH3-only proteins before or at the mitochondrial level and prevents the release of cytochrome c from the mitochondria in etoposidetreated cells (Kamesaki et al, 1993), and overexpression of heat shock protein (HSP) 27, that interferes with cytochrome c released from the mitochondria in the cytosol to prevent caspase-9 activation (Bruey et al, 2000), both prevented caspase-10 activation in etoposide-treated cells (Figure 6a), suggesting that cytochrome c is critical for etoposide-induced caspase-10 activation. Exposure of HeLa, 293T and U937 cells to Caspase-10 in drug-induced apoptosis R Filomenko et al arsenic trioxide, a compound that was shown to directly target the mitochondria to trigger the release of cytochrome c and downstream caspase cascade activation (Sordet et al, 2001), induced a decrease in caspase-10 proform level in these three cell types. Similar results were obtained with caspase-9 proform that served as a control (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability was monitored using trypan blue exclusion. Mitochondrial and cytosolic fractions were prepared as described (Sordet et al, 2001). The different fractions collected were frozen at À801C until use.…”
Section: Methodsmentioning
confidence: 99%